Perlindungan Hukum Karya Cipta dengan Teknologi Blockchain dalam Kerangka Hukum Hak Kekayaan Intelektual di Indonesia - Hadiwibowo, Yoga Teguh; Hasan, H. Umar; Rosmidah, Rosmidah (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
This study aims to analyze the effectiveness of legal protection for copyrighted works in Indonesia through the application of blockchain technology. The research method used is normative juridical with a regulatory approach and conceptual approach. The findings show that blockchain technology can enhance transparency and legal certainty in copyright protection. The implementation of blockchain allows for permanent and tamper-proof recording of ownership of copyrighted works, making it easier to prove ownership and usage, while reducing copyright infringements. However, despite its great potential, the application of blockchain in Indonesia faces regulatory challenges. Currently, there are no specific regulations regarding blockchain technology in copyright protection, which limits its effective implementation. These challenges include the lack of clear legal frameworks and the need for operational standards to be adopted. In conclusion, while blockchain technology can be an innovative solution for copyright protection, Indonesia requires regulatory updates to support its effective implementation. With clear regulations in place, blockchain technology can strengthen the copyright protection system and provide greater benefits for creators and copyright holders in Indonesia.